Hypoglycemia rates and glycemic hormonal response after laparoscopic Roux-en-Y gastric bypass versus sleeve gastrectomy: a meta-analysis of comparative studies - Sotirios Artsitas; Dimitrios Artsitas; Spyridon Smparounis; Dimitrios Theodorou; George C. Zografos (Bulletin of the National Research Centre, 2023)
Abstract Background This study aims to quantify the difference between Roux-en-Y gastric bypass (RYGB) and laparoscopic sleeve gastrectomy (LSG) concerning the incidence of post-bariatric surgery hypoglycemia (PBSH) and variations in glycemic homeostasis. Main body of the abstract A literature search was conducted between July and August 2023. Inclusion criteria involved studies exclusively in the English language that comparatively investigated the occurrence of postoperative hypoglycemia in patients undergoing the above two bariatric approaches. A total of 16 studies, comprising data from 1806 patients, were identified and classified based on 39 primary and secondary outcomes pertaining to the period following the first postoperative semester. Our findings reveal that patients undergoing gastric bypass have a 50% higher risk of developing postoperative hypoglycemia compared to those undergoing sleeve gastrectomy. Moreover, this risk doubles when questionnaire data are taken into account. Lower glucose levels (MD = − 10.54 mg/dl, CI95% = [− 16.63; − 4.45]) were observed in the RYGB group at 2 h after an oral glucose tolerance test (OGTT), which is considered a precursor to the development of PBSH. Higher zenith (MD = 49.11 mg/dl, CI95% = [16.12; 82.10]) and lower nadir plasma glucose levels (MD = − 5.70 mg/dl, CI95% = [− 10.03; − 1.37]) were also noted in the same group, with a wider glucose range (MD = 52.22 mg/dl, CI95% = [18.25; 86.19]). Lastly, no differences were observed in insulin and C-peptide levels, glycosylated hemoglobin (HbA1c), as well as insulin sensitivity score (HOMA-IR). Short conclusion Patients in the RYGB group are at least 50% more likely to develop postoperative hypoglycemia compared to those in the LSG group. Our analysis suggests a more unstable glycemic homeostasis mechanism, with a strong contribution from late dumping syndrome.